2007
DOI: 10.1900/rds.2007.4.85
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Skin Capillary Recruitment Precedes Chronic Complications in Patients with Type 1 Diabetes

Abstract: ■ AbstractMicrovascular function in patients with type 1 diabetes without chronic complications was assessed using skin capillary recruitment during post-occlusive reactive hyperemia (PORH). Structural (maximal) capillary density was evaluated during venous occlusion. The study included 48 consecutive outpatients aged 26.3 ± 10.8 years with type 1 diabetes (duration of 9.5 years) without chronic complications and 34 control subjects. Intravital capillary video-microscopy was used in the dynamic study of skin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
1
13
1
Order By: Relevance
“…Despite previous contradictory reports [ 42 , 43 ], our results showed that aerobic activity of low difficulty level, performed within the functional capacity of sedentary individuals, can promote significant increases in the microvascular density of T1D patients, who appear to have a severely compromised angiogenic process in the absence of exercise [ 44 , 45 ]. In fact, as shown by previous studies [ 12 , 46 ], and considering that sedentary T1D patients do not present with a capillary reserve in either the hands or feet [ 12 ], the changes in capillary density observed in the present study after exercise training suggest that low intensity aerobic exercise not only represents an important stimulus for increased capillary perfusion, it also contributes to increasing the number of capillaries.…”
Section: Discussionsupporting
confidence: 81%
“…Despite previous contradictory reports [ 42 , 43 ], our results showed that aerobic activity of low difficulty level, performed within the functional capacity of sedentary individuals, can promote significant increases in the microvascular density of T1D patients, who appear to have a severely compromised angiogenic process in the absence of exercise [ 44 , 45 ]. In fact, as shown by previous studies [ 12 , 46 ], and considering that sedentary T1D patients do not present with a capillary reserve in either the hands or feet [ 12 ], the changes in capillary density observed in the present study after exercise training suggest that low intensity aerobic exercise not only represents an important stimulus for increased capillary perfusion, it also contributes to increasing the number of capillaries.…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies using video-capillaroscopy, using the same methodology that was used in the present investigation, we showed that maximal capillary recruitment in younger healthy subjects ranged between 6 and 7% (Francischetti et al, 2011;Kaiser et al, 2013;Tibirica et al, 2007aTibirica et al, , 2007b, although we do not yet have any plausible explanation for this discrepancy. It is also noteworthy that basal values of capillary density (spontaneously perfused capillaries) in healthy volunteers can vary considerably between different studies.…”
Section: Discussioncontrasting
confidence: 43%
“…Posterior to the occurrence of beta-cell dysfunction in type 1 diabetes, numerous functional alterations in blood flow can be observed [13,14]. Early features of type 1 diabetes include endothelial dysfunction, increased leukocyte-endothelial adhesion [15], increased blood viscosity [16,17], and changes in the hemodynamic properties of red blood cells [18,19].…”
Section: Endothelial Function and Microvascular Blood Flow In Type 1 mentioning
confidence: 99%